MEKANISME KOPING KELUARGA DENGAN SAKIT KRONIS: SEBUAH STUDI FENOMENOLOGI - admin ilkes (STIKES Karya Husada Kediri, 2017)
Living with a chronic illness are challenged by anxiety, stress, physical fatigued and emotional strain that accompanies the daily activities of caregiving. Family capacity to adapt with this conditions depend on their coping mechanism and available resources. The aim of this research is to describe family coping in attending the challenges of chronic illness. The research method used was descriptive phenomenological approach. Using purposive-sampling, eight families living with chronic illness were participated in this study. Results of this research is individual coping, family strength and community support were related to maintaining family balance and adaptive response of family. The result is expected to be recommendation in improving nursing care in families with chronic illness. Providing family with adequate information about illness and family counseling can improve family coping.